PENINGKATAN KECERDASAN ANAK MELALUI PEMBERIAN ASI DALAM AL-QUR’AN - Hanafi, Yusuf (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2012)
Todays health researchs prove that the breast milk contains a lot of content that is not found in milk formula, especially immunologic substances. Breast milk contains anti-infective agents that are clean and free of contamination. Immune substances that exist in immunoglobulins, secretory, and lactoferrin as well as the presence of factors that can stimulate Lactobacillus bifidus to protect baby?s digestive tract. Lately also known that breast milk can increase children?s intelligence. It could be due to nutritional milk, methods, or durations of breastfeeding. Research shows that a Taurine, Decosahexanoic acid (DHA) and Arachidonic acid (AA) exist in breast milk is very useful in the formation of the baby?s brain cells and accelerate the stimulus from the receptor organ to the brain, so that the response can be given in a fast time. Yet long before the WHO, researchers and human rights activists has been intensifying exclusive breastfeeding, the Koran was first called to breastfeed h}awlayn kâmilayn two full years. The Relevances between the activity of breastfeeding for two full years and the brain development of baby will be discussed in this paper.